"Malignant" Perivascular Epithelioid Cell Neoplasm: Risk Stratification and Treatment Strategies. (26th April 2012) - Bleeker, Jonathan S.; Quevedo, J. Fernando; Folpe, Andrew L.
Abstract : Purpose . Perivascular epithelioid cell tumors (PEComas) are a rare collection of tumors characterized by a myomelanocytic phenotype, and PEComas occurring in "nonclassic" anatomic distributions are known as perivascular epithelioid cell tumor not otherwise specified (PEComa-NOS). This review aims to compile and analyze cases of PEComa-NOS in an effort to better define their natural history. Design . We evaluated all 234 cases of PEComa-NOS reported in the English literature, extracting information regarding diagnostic features, treatment approaches, and outcomes. Multivariate analysis of a number of variables evaluable on pathologic review was performed to refine preexisting risk stratification criteria. Outcomes for patients receiving nonsurgical treatment are also reported. Results . Primary tumor size ≥5 cm (P = 0.02 ) and a high (1/50 HPF) mitotic rate (P < 0.0001 ) were the only factors significantly associated with recurrence following surgical resection. Cytotoxic chemotherapy and radiation therapy have shown little benefit in treating PEComa-NOS; mTOR inhibition is emerging as a treatment option. Conclusion . Progress has been made in understanding the natural history and molecular biology of PEComa-NOS. This review further clarifies risk of recurrence in this disease, allowing clinicians to better risk stratify patients. Further work should focus on applying this knowledge to making treatment decisions for patients with this disease.